‘Outlanders’ Saved in the Roman Triumphs: The Fate of Prominent Captives in Rome at the Close of the Republic and in the Principate - BALBUZA, Katarzyna (Katolicki Uniwersytet Lubelski Jana Pawła II, 2020)
One of the forms of expression of the Roman ideology of victory in the Principate was a triumph (triumphus curulis), during which barbaric captives, often of a high political status, were exposed. According to the tradition, they should have been put to death during the triumph, which was of ritual and symbolic significance. The analyzed examples of the most prominent foreign captives from the late Republic and Principate show that sentencing the captives to death was much less frequent in the Principate. Thanks to mercy (clementia) shown by the emperors, captives frequently saved their lives. They did not reject an offered chance for further life in the Roman Empire, and they often asked for it. Such an attitude did not have to mean giving up personal dignity. Romans allowed them to function normally in the Roman Empire, to educate, obtain Roman citizenship, further develop according to individual characteristics, and be promoted socially and politically. Jednym ze środków wyrazu rzymskiej ideologii zwycięstwa epoki pryncypatu był triumf (łac. triumphus curulis), w trakcie którego eksponowani byli jeńcy barbarzyńscy, nierzadko o wysokim statusie politycznym. Według tradycji powinni oni ponieść śmierć podczas triumfu, co miało znaczenie rytualne i symboliczne. Przeanalizowane przykłady najznamienitszych jeńców obcego pochodzenia z końca republiki i okresu pryncypatu dowodzą, że częściej aniżeli za republiki rezygnowano w epoce pryncypatu ze skazywania ich na śmierć. Dzięki łasce (łac. clementia) okazywanej przez cesarzy jeńcy często zachowywali życie. Nie tylko nie odrzucali oferowanej im szansy na dalsze życie w państwie rzymskim, ale nierzadko sami o nią prosili. Taka postawa nie musiała oznaczać rezygnacji z godności osobistej. Rzymianie umożliwiali im normalne funkcjonowanie w państwie rzymskim, edukację, zdobycie obywatelstwa rzymskiego, dalszy rozwój zgodnie z indywidualnymi predyspozycjami, awans społeczny i polityczny.